Circular vs. linear stapling after minimally invasive and robotic-assisted esophagectomy: a pooled analysis : systematic reviews and meta-analyses - Finze, Alida; Betzler, Johanna; Hetjens, Svetlana; Reißfelder, Christoph; Otto, Mirko; Blank, Susanne (Langenbeck's archives of surgery, 2022)
Current data states that most likely there are differences in postoperative complications regarding linear and circular stapling in open esophagectomy. This, however, has not yet been summarized and overviewed for minimally invasive esophagectomy, which is being performed increasingly.